The Feed the Future Rwanda Orange-fleshed Sweetpotato (OFSP) for Income and Nutrition Activity - International Potato Center (2017)
At the end of its second year, this going-to-scale project in 10 districts of Rwanda has directly reached over 125,000 households with OFSP. DVMs have sold vines worth US $300,747. Roots producers have sold sweetpotato roots worth US $99,984 and households have consumed 7,495 tons of OFSP roots.